2014
DOI: 10.1158/1078-0432.ccr-14-1768
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Landscape of Aggressive Cutaneous Squamous Cell Carcinoma

Abstract: Purpose Aggressive cutaneous squamous cell carcinoma (cSCC) is often a disfiguring and lethal disease. Very little is currently known about the mutations that drive aggressive cSCC. Experimental Design Whole exome sequencing was performed on 39 cases of aggressive cSCC to identify driver genes and novel therapeutic targets. Significantly mutated genes were identified with MutSig or complementary methods developed to specifically identify candidate tumor suppressors based upon their inactivating mutation bias… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
627
3
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 536 publications
(695 citation statements)
references
References 33 publications
47
627
3
18
Order By: Relevance
“…It is possible that additional mechanisms might contribute to the regulation of RNF144A. During the preparation of this manuscript, two more somatic mutations, A255fs*30 and L260M, were identified on the TM domain (37,38). It would be very interesting to investigate the potential effects of these somatic mutations.…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that additional mechanisms might contribute to the regulation of RNF144A. During the preparation of this manuscript, two more somatic mutations, A255fs*30 and L260M, were identified on the TM domain (37,38). It would be very interesting to investigate the potential effects of these somatic mutations.…”
Section: Discussionmentioning
confidence: 98%
“…(132) One of the major recognised cellular drivers of SCC is loss of function of the tumour suppressor gene TP53. Data supports a strong correlation between solar ultraviolet radiation (UVR) and mutational burden in the p53 gene with up to 90% of squamous cell carcinomas exhibiting p53 mutations.…”
Section: Genetic Profile Of Cscchn With and Without Pnsmentioning
confidence: 99%
“…(132) The authors concluded that the mutational signature of advanced cSCC is similar to mucosal HNSCC and dominated by tumour suppressor genes, with 8 of the top mutated genes shared between these tumour types. Similarly, an earlier study by Dooley et al (2003) found genetic profiles between oral SCC cell lines and facial cutaneous SCC cell lines to be highly similar across 23…”
Section: Genetic Profile Of Cscchn With and Without Pnsmentioning
confidence: 99%
“…Interestingly, mutations in WNT/β-catenin signaling components are generally rare in SCC tumours, including cSCC (Doglioni, et al 2003;Li, et al 2015;Pickering, et al 2014). For example in oesophageal SCC, the frequency of ctnnb1 mutations is only 1.1%, but yet 86.4% of oesophageal SCC tumours contain mutated WNT pathway genes (Song, et al 2014), suggesting the mechanisms by which WNT signaling function is peterbed in SCC tumours, are potentially diverse.…”
Section: Wnt Signaling In Csccmentioning
confidence: 99%